Kreis, Annelies, Wick, Jeannette & Kosorok Labhart, Carmen (Hrsg.) (2016). Kooperation im Kontext schulischer Heterogenität. - Kummer Wyss, Annemarie (Swiss Journal of Educational Research, 2018)
Rezension